DOES OWNERSHIP MODERATE THE FINANCIAL PERFORMANCE AND CSR DISCLOSURE LINKAGE? - Irvan, Muhammad Alif Nur; An Nurrahmawati; Elsa Amalia (Faculty of Economics and Business University of Mataram, 2025)
This study examines the effect of financial performance on corporate social responsibility (CSR) disclosure by considering the moderating role of ownership structure, including institutional, family, foreign, and managerial ownership. The research is motivated by inconsistent empirical findings regarding the relationship between profitability and CSR disclosure in developing countries, particularly in controversial industries facing high legitimacy pressures. The sample consists of 102 firm-year observations of companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The analysis employs Random-Effects Generalized Least Squares (GLS) panel regression with a lag-1 ROA as the k-test variable. The results reveal that Return on Assets (ROA) has a positive effect on CSR disclosure, consistent with legitimacy theory, which posits that sound financial performance enhances social transparency. However, managerial ownership weakens this relationship, whereas institutional, family, and foreign ownerships do not exhibit significant moderating effects. These findings underscore the importance of ownership characteristics in influencing CSR disclosure practices and provide implications for regulators and investors in strengthening corporate accountability, particularly in firms with dominant managerial ownership.